PEMBERDAYAAN SANTRI PONDOK PESANTREN MUSTHAFAWIYAH DI ERA GLOBALISASI (Studi Kasus Pondok Pesantren Musthafawiyah) - Anto, Rudi Hary (STAI Hubbulwathan Duri, 2017)
Holistically the survival of Pondok Pesantren Musthafawiyah until now because of spiritual, intellectual and social empowerment is done by way of simplicity. The nature of simplicity and tradition that is in Pondok Pesantren Musthafawiyah increasingly will experience obstacles due to the increasingly sophisticated globalization and can not be inhibited. The Mustahawiyah pesantren which was founded in 1912 still maintains its traditional system. This can be seen from the santri uniform consisting of: sarong cloth, ordinary white clothes, white cap and wear sandals. This is what makes sense of togetherness among fellow santri without any sense of difference. Based on the observation, empowerment in Pondok Pesantren Musthafawiyah includes empowerment of Ruhaniah, Intlektual and Sosial. This fact is very interesting to be a comparison material to the modern pesantren-pesantren around Mandailing Natal district.